The placebo and nocebo effects in functional urology - Mostafaei, Hadi; Jilch, Sandra; Carlin, Greta Lisa; Mori, Keiichiro; Quhal, Fahad; Pradere, Benjamin; Laukhtina, Ekaterina; Schuettfort, Victor M; Aydh, Abdulmajeed; Sari Motlagh, Reza; Roehrborn, Claus G; Shariat, Shahrokh F; et al. (Nature reviews. Urology, 2022)
A placebo is an inert substance normally used in clinical trials for comparison with an active substance. However, a placebo has been shown to have an effect on its own; commonly known as the placebo effect. A placebo is an essential component in the design of conclusive clinical trials but has itself become the focus of intense research. The placebo effect is partly the result of positive expectations of the recipient on the state of health. Conversely, a nocebo effect is when negative expectations from a substance lead to poor treatment outcomes and/or adverse events. Randomized controlled trials in functional urology have demonstrated the importance of the placebo and nocebo effects across different diseases such as overactive bladder, urinary incontinence, lower urinary tract symptoms and interstitial cystitis/painful bladder syndrome, as well as male and female sexual dysfunction. Understanding the true nature of the placebo-nocebo complex and the scope of its effect in functional urology could help urologists to maximize the positive effects of this phenomenon while minimizing its potentially negative effects.
Keywords: symptomy dolních močových cest; Male; mužské pohlaví; výsledek terapie; Lower Urinary Tract Symptoms; Female; nocebo efekt; Placebo Effect; Treatment Outcome; Humans; ženské pohlaví; Nocebo Effect; placebo efekt; urologie; lidé; Urology